ANALISIS iPREFERENSI iKONSUMEN iDALAM iPEMBELIAN iBUAH MANGGAi GEDONGi GINCUi DIi PASARi TRADISIONALi KADIPATEN KABUPATEN MAJALENGKA - Sapara, Nadia; Rosyad, Anisur; Wijayanti, Irene Kartika Eka (Universitas Galuh, 2023)
Gedong gincu mango is one of tropical fruit plants produced in Majalengka Regency. Kadipaten traditional market in Majalengka Regency is the center of Gedong gincu mango commodity. During the decision-makingaprocess, consumersawill choose fruits according toatheir preferences.aTherefore, itais necessaryato conductaresearch toadetermine theacharacteristicsaof consumerapreferences and to analyzeathe extentato whichathese preferencesaaffectapurchasing decision for Gedongagincu mango. This study aimed to: (1) identify the attributes most considered by consumers in purchasing decision for Gedong gincu mango at the Kadipaten market and (2) identify the attributes that become preferences in purchasing decision for Gedong gincu mango at the Kadipaten Market. The research was conducted at the Kadipaten traditional market, Majalengka Regency from October to November 2022. Sampling was carried out using the Accidental Sampling technique with the total of 100 respondents. Data analysis used were Cochran test and conjoint test. The results of the Cochran analysis showed that the attributes considered in purchasing Gedong gincu mango were taste, skin color, and price, while the Conjoint analysis showed that consumer preferences for the attributes and sub-attributes of Gedong gincu mango were yellow redness skin color, sweet and sour taste, and the price of Rp. 20,000 per kg - Rp.25000 per kg.